Corporate Governance: An Indian Perspective on Disclosure and Transparency Issues - Kaur, Jatinder; Pareek, Ashish; Upadhaya, Gitanjali (Journal of Contemporary Research in Management (JCRM), 2014)
The fundamental base of corporate governance is the agency theory which states that there is separation between ownership and control. This separation creates divergence in the interests of various parties involved including management and stakeholders, generating agency problem. In particular, better disclosures are considered to be the better way to reduce the agency problem. Corporate governance appends transparency and disclosure of corporate structure to ensure accountability of management towards shareholders. This paper sets out to examine the disclosure practices adopted by the Indian banking sector. A composite disclosure checklist consisting of more than 104 items is developed including both mandatory and non-mandatory items. Disclosure checklist is formulated on the basis of existing literature, various corporate governance index formulated by previous researchers, norms of Clause 49 of Listing Agreement. The recommendations of Clause 49 were incorporate by Kumar Manglam Birla Committee laid down by SEBI. The findings of the study indicates that Indian banking sector is compliant with the mandatory disclosure practices but not enough to hit the highest point. Also, banks are on the path to the adoption of and making disclosures regarding voluntary recommendations. This paper is an attempt to contribute to the academic literature by illustrating that a strict check by regulatory authorities brings the prospective for high compliance regarding disclosure and transparency.